The Nexus Between Financial Standing and Sustainable Entrepreneurship: Insights from Poland - Kowalska, Magdalena; Misztal, Anna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
This paper analyses the relationship between financial standing and sustainable entrepreneurship in Poland from 2008–2022. In a broad economic context, understanding how financial stability influences sustainable business development is crucial for fostering long-term economic resilience. To quantify these concepts, synthetic indicators of financial standing and sustainable entrepreneurship are constructed using a variable normalization method. The econometric analysis employs Ordinary Least Squares (OLS) and Seemingly Unrelated Regression (SUR) models to capture the general effect and potential interdependencies across different sustainability dimensions. The OLS results indicate a statistically significant (<0.05) positive relationship between financial standing and sustainable entrepreneurship, suggesting that improved financial conditions support sustainable business practices. However, the SUR model reveals a more complex structure, with varying effects across different sustainability pillars, indicating that financial standing does not uniformly influence all aspects of sustainable entrepreneurship. These findings highlight the necessity of a differentiated policy approach to financial support mechanisms, recognizing that the impact of financial stability is not homogenous. Policymakers should consider tailored financial instruments to enhance sustainable entrepreneurship while addressing specific sectoral needs. Further research could extend this framework to other EU countries, examining cross-country differences and dynamic interactions in broader macroeconomic conditions.